One hundred innovations for development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
One hundred Innovations for Development, ISBN 1 85339 095 X, 80pp, A4 format, UKL6.95 plus UKL1.40 post and packing from: